Politics Comes from Daily Life Reflections (Armada Riyanto Political Philosophy Perspective) - Juli Antonius Sihotang (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2021)
This article aims at exploring and describing the chaotic world of Indonesian politics which has often become a theme of public discussion especially politicians in many events. Problems focused on the world of politics were campaigns, debates, tactics and arguments from politicians. It makes the world of politics often show the winners and the losers. Whereas the real world of politics is also a realm to reflect on daily life. In reflecting, a politician was invited to explore the nobility of his dignity and others. He was brought to discover the depths of his life with others while at the same time discovering the truth. This discovery made a politician realize that the world of politics was not only about campaigns, debates, tactics and arguments. In order to gain this problem, the theoretical reference from Armada Riyanto's thinking was used. The data were collected by the author through a literature study and analyzed qualitatively by collecting and studying various books, journal articles, and other sources related to the author's articles. Hence, the differences, similarities, and novelties of the author's articles could be seen. This study concluded that the depth of life and truth guides a politician not to be naive in following orders, carrying out the law, and which politicians must be defeated in tactics and strategies. Politics should be synonymous with honesty, justice, and brotherhood among politicians.